PERLINDUNGAN HUKUM TERHADAP KONSUMEN KORBAN KARTEL PRODUSEN KENDARAAN BERMOTOR YAMAHA-HONDA DALAM PERSPEKTIF UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN (STUDI KASUS PUTUSAN NOMOR 04/KPPU-I/2016) - Wahyu Alisa Putri; Mariske Myeke Tampi (Fakultas Hukum Universitas Tarumanagara, 2020)
Competition in business is a common thing experienced by business actors, especially when healthy competition will have a positive impact and benefit consumers. Conversely, if it is done unhealthily and monoplically, it will have a negative impact that can harm consumers. One of the cases of unfair competition handled by the KPPU was the case of the Yamaha-Honda motorcycle cartel in the case of Decision Number 04 / KPPU-I / 2016. The decision is deemed not to protect consumers because the KPPU determines compensation to the state,not to consumers as the party who is injured by the cartel. KPPU does not have the function of protecting consumers for cartel victims because legally it is not under the authority of the KKPU, but under the authority of BPKN regarding consumer protection issues. The separation of the legal rules regarding business competition and consumer protection which results in the limitation of the KPPU's authority to be unable to carry out tasks beyond its authority, except those that have been regulated in law. The compensation mechanism for victims of the Yamaha-Honda cartel is through class action lawsuits and citizen lawsuits. However, this lawsuit is quite difficult to carry out because it reflects on the consumer's lawsuit in the case of decision Number 526 / Pdt.G / 2019 / PN.Jkt.Pst, of which many of the claims were broken due to difficulties in proving the losses suffered by each consumer.